EFEKTIVITAS PENAMBAHAN GULA TERHADAP KUALITAS NATA DE CASSAVA DARI LIMBAH CAIR TAPIOKA SEBAGAI PENGEMBANGAN MODUL PADA KONSEP BIOTEKNOLOGI KONVENSIONAL KELAS XII SMA - Nurlinda '; Darmawati '; Imam Mahadi Mahadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This research aimed to the effectiveness sugar addition of nata de cassava quality from tapioca liquid waste on April to June 2015, for learning module development of biology on conventional biotechnology concept grade XII Senior High School. The research conducted with 2 phases namely experimental research and development of learning module. Experimental research was using non factorial completely randomized design that consist 5 treatments and 3 replicates and totally obtain 15 experimental design. It would further DMRT test if real different. The observed parameters include crude fiber content, thickness and organoleptic texture, smell, color and flavor. The result showed that sugar addition significantly influence to the crude fiber content and thickness of nata de cassava from tapioca liquid waste. The addition 15 % of sugar that can produce the best crude fiber content, thickness, texture and preference. The result of crude fiber content is 2.62% and the resulting thickness is 1.54 cm. Rate results of learning module of biology development on conventional biotechnology concept grade XII Senior High School is valid. Keywords: The addition of sugar, Nata de Cassava, Tapioca Liquid Waste, Learning Module